Deformities of the Thoracic Wall: Don't Forget the Plastic Surgeon - Schwabegger, Anton Herbert (European Journal of Pediatric Surgery, 2018)
Surgical procedures for pectus excavatum (PE) repair, such as minimally invasive repair of pectus excavatum or similar interventions (modified open videoendoscopically assisted repair of pectus excavatum), for remodeling the anterior thoracic wall may finally not always achieve sufficiently pleasing aesthetic results. Particularly in the asymmetric and polymorphic cases, remnant deformities may still be present after any sophisticated remodeling attempt. On the other hand, some cases despite optimal surgical management develop mild recurrences with partial concavity or rib cartilage distortion shortly after pectus-bar removal. Secondary treatment options then may include open access surgery, resection, or reshaping of deformed and prominent costal cartilage. Residual concave areas can be filled by autologous tissue, such as cartilage chips, liposhifting, or implantation of customized alloplastics. To provide the best options for a variety of primary or secondary postsurgical expressions of anterior wall deformities, any physician dealing with PE corrections should be familiar with various shaping and complementary reconstructive techniques or at least should have knowledge of such. However, among treating surgeons, there is an awareness that no single method can be applied for every kind of funnel chest deformity. Careful selection of appropriate techniques, either as a single approach for the ordinary deformities or in conjunction with ancillary procedures for the intricate cases, should be mandatory, based on the heterogeneity of symptoms, severity, expectations, and surgical and technical resources. A variety of such ancillary reconstructive procedures for PE repair are explained and illustrated herewith.
Keywords: congenital; thoracic wall deformity; refinement; adjuvant remodeling; aesthetic surgery